Developing "My Plate" Poster as a Nutrition Education Media of Pregnant Women in Efforts to Prevent Stunting - hesti Atasasih; Alkausyari Aziz (STIKes Hang Tuah Pekanbaru, 2021)
One of nutritional problems experienced by toddlers is stunting, which is a short or very short body condition in children due to chronic malnutrition that occurs from pregnant women to children aged 2 years. Nutrition education is a method and effort to increase knowledge of nutrition and eating behavior in order to create optimal nutritional status. Education for the "My Plate" poster is important for pregnant women to implement a healthy diet and to meet daily nutritional needs as an effort to prevent stunting. This research was conducted by interview method. From the result of this research, a poster of "My Plate-Pregnant Women" has been designed as a nutrition education media.   Keywords: Nutriotion Education Poster, Pregnant Women, Stunting